Analyzing Volunteering and Humanitarian Work Policy In the United Arab Emirates and its Role in Promoting Sustainable Development - Salman, Muna (The Arab Journal of Administration, 2023)
The policy brief aims to analyze volunteering and humanitarian action policy and its impact on promoting sustainable development in the United Arab Emirates. Its importance lies in shedding light on the efforts and activities of the UAE government to empower youth to deal with the changes brought about by globalization, and to support charitable and volunteer bodies, by drafting appropriate legislation, strategies and social policies to make volunteering and humanitarian work a life practice in the country. The analytical results revealed that the UAE is one of most involved countries in volunteer and humanitarian work, as it achieved a leading position and maintained the first place in the world as the largest donor of official development assistance for more than five consecutive years. In addition, there are exceptional efforts and initiatives at all levels to promote the concept of voluntary and humanitarian work. The results also found a positive relationship between the policies set by the government and directing the volunteer work, between it and the increase in the number of volunteers in local initiatives between both genders, and the high statistics of voluntary and humanitarian work. which is positively reflected in promoting sustainable development and preserving the country’s position globally. The summary concluded with a number of recommendations, the most prominent of which are: Providing extensive resources and information on volunteer and humanitarian work policy in the UAE for all segments of society, setting clear and specific legislations to guarantee the rights of the parties involved in the volunteering process, and expanding campaigns directing Emirati youth to engage more in humanitarian, volunteer, sacrifice, and altruistic work and promoting the spirit of humanitarian work, preparing training and educational workshops to raise the percentage of volunteers, and awareness-raising workshops for parents, expanding the base of youth circles participating in decision-making to formulate effective policies for volunteering and humanitarian work, activating the role of women in humanitarian work in all its forms, and finally focusing on the emerging category of volunteer work and conducting prospective studies to measure the most important factors that help activate the voluntary and humanitarian policy positively to promote sustainable development.